Constructing and Implementing a “Tri-Phase-Tri-Dimensional” Digital Assessment System for Junior High School English Academic Quality - Sun, Yuwen; Yin, Ming (Journal of Educational Research and Policies, 2025)
Junior high school English plays a critical role in fostering students’ comprehensive development and enhancing teaching quality in China. Traditional evaluation methods struggle to meet the core competency requirements outlined in the English Curriculum Standards for Compulsory Education. This study, grounded in the New National English Curriculum Standards and the China Standards of English Language Ability, proposes a “Tri-Phase-Tri-Dimensional” digital assessment system that integrates formative, process-oriented, and summative evaluations. By leveraging intelligent tools, the system enables multidimensional data collection, real-time feedback, and personalized interventions. A case study demonstrated the system’s efficacy, with data revealing a 15.5% improvement in language skills and a 20.8% enhancement in learning competencies, a 48.2% reduction in teachers' grading workload, and 92.1% of students achieving the targeted speaking proficiency. The study concludes that the “Tri-Phase-Tri-Dimensional” digital assessment system represents a systematic and theoretically robust model that significantly enhances the scientific validity and effectiveness of English academic quality evaluation, offering a practical solution for improving teaching quality and a scalable framework for assessment reform.